Utility of Antinuclear Antibody Screening by Various Methods in a Clinical Laboratory Patient Cohort. (1st July 2016) - Deng, Xiaoli; Peters, Brian; Ettore, Michael W; Ashworth, Judy; Brunelle, Lynn A; Crowson, Cynthia S; Moder, Kevin G; Snyder, Melissa R
Abstract: Background: Antinuclear antibody (ANA) 5 testing is routinely performed during evaluation of patients with a suspected connective tissue disease (CTD), yet the question of which method is most appropriate remains controversial. The purpose of this study was to evaluate the clinical utility of ANA testing by an enzyme immunoassay (EIA), an immunofluorescence assay (IFA), and a multiplex immunoassay (MIA) in a routine laboratory population. Methods: Samples (n = 1000) were collected from specimens submitted for ANA testing by EIA (Bio-Rad). All samples were subsequently analyzed by IFA (Zeus) and MIA (Bio-Rad). The sample cohort was weighted to represent the routine testing population. Diagnostic information was obtained by chart review. Results: For the diagnosis of a CTD, ROC curve analysis demonstrated no significant differences between IFA (area under the curve 0.81) and EIA (0.84) ( P = 0.25), with overlay of a single point for the MIA. When normalized to a specificity of approximately 90%, the sensitivities of the MIA, EIA, and IFA were 67%, 67%, and 56%, respectively. By varying the clinical cutoff, the IFA could achieve the highest sensitivity of 94%; however, the corresponding specificity was only 43%. In contrast, a strongly positive EIA had a specificity of 97%, although, at this cutoff, the sensitivity was only 40%. Conclusions: Although the overall diagnostic performance of the IFA, EIA, and MIA were not statistically different, the clinical sensitivity and specificity varied dramatically based on the positive/negative cutoff. Knowledge about the performance characteristics of each method will significantly aid in the interpretation of ANA testing.